Post Operative Histological Evaluation of Perineural Invasion in Patients Diagnosed with Oral Squamous Cell Carcinoma with No Clinical Signs and Symptoms of Nerve Involvement Pre-Operatively at a Tertiary Care Hospital - Younus, Misbah; Ahmed, Sufyan; Naushad, Zainab; Ghulam, Farwa; Fatima, Asar; Zaheer, Alina (Indus Journal of Bioscience Research, 2025)
Oral Squamous cell carcinoma (OSCC) has highest incidence of morbidity and mortality globally. Perineural invasion (PNI) is the main histological feature linked to poor prognosis of OSCC, however, it is usually missed in those patients who do not have any neurological symptoms prior to surgery. Therefore, the aim of this study was to evaluate histological characteristics of perineural invasion in oral squamous cell carcinoma patients who has no sign and symptoms of nerve involvement pre-operatively at tertiary care hospital. This was a cross—sectional study with total population of fifty-five (55) patients, conducted from July 2024 to December 2024 at Abbasi Shaheed Hospital, Karachi. The tissue sample from perineural space, post-surgery was collected from the participants who gives consent to participate and was then sent for histopathologic examination. All the histological information with the demographics and history of patients were recorded and the data was analyzed using SPSS version 23. The mean age of participants was 57.4±10.1 years with more males having 67.3% habit of tobacco chewing and 54.5% habit of smoking. Based on histopathological evaluation, 15 patients were positive for perineural invasion, among which 46.7% experience recurrence. We can conclude that PNI can be present in OSCC patients without pre-operative neurological symptoms therefore, early detection of PNI may improve prognostic accuracy and adjuvant treatment strategies.